PENINGKATAN PEMBELAJARAN BOLA VOLI MELALUI METODE PENDEKATAN TAKTIK SISWA SEKOLAH MENENGAH PERTAMA - Samodro, Harri Ditya (Fakultas Ilmu Keolahragaan Universitas Negeri Malang, 2020)
This study aimed to improve the learning outcomes of volleyball games in the seventh graders of SMP Negeri 3 Nglipar through tactical approach methods .This study was a classroom action research (CAR) consisting of two cycles. Each cycle consisted of four stages: preparation, implementation, observation, and evaluation. The object of the study was 16 seventh graders of SMP Negeri 3 Nglipar. Analysis of research results was carried out in a qualitative descriptive method. The research was conducted on the even semester of 2017/2018 school year. The action was taken in the form of a tactical approach method in learning volleyball under-passing. Data retrieval instruments in this study used performance tests and observations. The performance tests were carried out to assess the skills and affective aspects of students, while the observations were made to determine the implementation of learning activities. The results showed that through the tactical approach method in learning, there was an increase in students’ learning outcomes in under-passing material of volleyball game. The final test results showed that the average score of students was 78.9 with the percentage of Passing Grade achievement reaching 94%.